1933
DOI: 10.1172/jci100544
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digitalis on the Venous Pressure of Normal Individuals

Abstract: That the admiinistration of digitalis in heart failure causes an increase in cardiac output (per minute and per beat) and a fall in venous pressure is well known (1). It is also well establislhed that the exhibition of digitalis to normiial meni and dogs results in a decrease(l output (2, 3, 4, 5, 6, Ini )fl:.l Stewart and Cohn (7) found a marked fall in venous pressure in one normiial subject after oral administration of digitan, using the Mioritz-Tabora (20) technlique of venous pressure determination. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1934
1934
1959
1959

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Both groups, however, observed a few cases in which the right atrial pressure fell without any significant change in cardiac output. This pressurereducing action was frequent enough to suggest that it might play a primary role; and this view was supported by (1) simultaneous observations that venesection might cause an increase in cardiac output of the same order as that produced by digoxin, and by (2) published work suggesting that digitalis reduced venous pressure in normal animals (Dock and Tainter, 1930) and in man (Rytand, 1933). This conception had the additional attraction of offering a possible explanation for some of the failures of digitalis therapy in certain instances of " high output heart failure " in which increased venous pressure was perhaps compensatory in nature.…”
mentioning
confidence: 89%
“…Both groups, however, observed a few cases in which the right atrial pressure fell without any significant change in cardiac output. This pressurereducing action was frequent enough to suggest that it might play a primary role; and this view was supported by (1) simultaneous observations that venesection might cause an increase in cardiac output of the same order as that produced by digoxin, and by (2) published work suggesting that digitalis reduced venous pressure in normal animals (Dock and Tainter, 1930) and in man (Rytand, 1933). This conception had the additional attraction of offering a possible explanation for some of the failures of digitalis therapy in certain instances of " high output heart failure " in which increased venous pressure was perhaps compensatory in nature.…”
mentioning
confidence: 89%
“…On the other hand, Dock and Tainter [1930], Tainter and Dock [1930], and Katz, Rodbard, Friend and Rottersman [1938] found that therapeutic doses of digitalis in normal dogs caused a lowering of venous pressure. Rytand [1933] studied 8 normal human subjects and concluded that digitalis decreased venous pressure; the fall was so slight, however, that its significance was difficult to evaluate. McMichael and Sharpey-Schafer [1944] found that intravenous injection of therapeutic doses of digoxin lowered the mean right atrial pressure of 3 normal human subjects.…”
Section: Methodsmentioning
confidence: 99%